Preconceito e discriminação racial no varejo: percepções e reações dos consumidores - Silva Junior, Adelson Ferreira da (2016)
This dissertation seeks to deepen the understanding of how the phenomenon of prejudice and racial discrimination is developed, perceived and faced in brick and mortar stores during the consumer and seller interaction. The comparison of existing knowledge in the literature, combined with an interpretative qualitative empirical research performed with black consumers in the metropolitan area of São Paulo, has generated valuable contributions to the understanding of the theme in question, and to put in question current consumer approach practices adopted by the retailers. It is found that this phenomenon, in the way it is perceived in the context of this research, in some cases shows different of some proposals presented in the literature. Among the four main themes that emerged, some aspects are highlighted: 1) while recognizing the existence of the phenomenon and despite the reports that make them evident, most respondents hesitate and deny its occurrence with themselves, transmitting great discomfort in dealing with the issue; 2) it is noticed that the mechanisms of social categorization based on social identity theory (SIT), the theoretical framework adopted in this research, operate in the context studied, but are insufficient to understand how being the agent (the seller) of the same group (ingroup) of the target (the final consumer) discriminatory behaviors are still perceived against them; 3) given the perception that the phenomenon manifests itself in its most subtle forms, the main dilemma experienced by respondents is to distinguish a bad service from a discriminatory treatment; and 4) besides the prevalence of passive reactions to the phenomenon, there is great importance attached by respondents to the appearance and self-image adjustments, as a defense mechanism to deal with possible incidents of prejudice and discrimination. The phenomenon in question in the retail environment is a serious problem that mainly affects the target, but also impacts everyone involved and seems to pervade other social spheres. The difficulties to face it range from the dubious way by which it usually manifests, hindering its recognition, to the often seemingly passive reactions from the target. From these findings, the dissertation draws attention to the relevant and unpublished aspects on consumer-seller interaction in physical stores, not yet explored in the Brazilian context and that need to be deepened. As managerial implications, the research calls attention of the retailers about the importance of formulating strategies to prepare physical stores sales teams to face properly the threats posed by the phenomenon. Finally, in terms of public policies, the results contribute to the improvement of not only educational communication efforts aimed to a fairer consumption relationship between consumers and sellers, but also to reduce the existing and still intense phenomenon of racial prejudice and discrimination in Brazil.